2018
DOI: 10.1002/1873-3468.12974
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in microRNA‐17‐92 dynamics accounts for differential nature of cellular proliferation

Abstract: MicroRNAs associated with the mir-17-92 cluster are crucial regulators of the mammalian cell cycle, as they inhibit transcription factors related to the E2F family that tightly control decision-making events for a cell to commit for active cellular proliferation. Intriguingly, in many solid cancers, these mir-17-92 cluster members are overexpressed, whereas in some hematopoietic cancers they are down-regulated. Our proposed model of the Myc/E2F/mir-17-92 network demonstrates that the differential expression pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…MiR-19b is an important part of miR-17/92 cluster and decreased expression of miR-19b may cause the defect of ventricular septal and short life span in mice. 7 Moreover, it was reported as an antithrombotic factor in IHD patients and a potential biomarker of human cell ageing. 8,9 Previous study also indicated that miR-19b attenuate endothelial cell apoptosis which is induced by tumour necrosis factor-α (TNF-α) and play role in cardiac fibroblast proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-19b is an important part of miR-17/92 cluster and decreased expression of miR-19b may cause the defect of ventricular septal and short life span in mice. 7 Moreover, it was reported as an antithrombotic factor in IHD patients and a potential biomarker of human cell ageing. 8,9 Previous study also indicated that miR-19b attenuate endothelial cell apoptosis which is induced by tumour necrosis factor-α (TNF-α) and play role in cardiac fibroblast proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐19b is an important part of miR‐17/92 cluster and decreased expression of miR‐19b may cause the defect of ventricular septal and short life span in mice 7 . Moreover, it was reported as an antithrombotic factor in IHD patients and a potential biomarker of human cell ageing 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…MiRs have been exquisitely described to control gene expression by binding to mRNA targets using the seed sequences, and miRs with the same or similar seed sequences and origin are grouped into one family or cluster [ 15 ]. The miR-17 family consists of the miR-17-92 cluster, miR-106a-363 cluster and miR-106b-25 cluster [ 17 ], and the miR-17 family has been well documented to influence the survival, differentiation and functions of various kinds of mammalian cells [ 18 , 19 ]. However, the effects of miRs associated with the miR-17 family in myogenesis are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-7153-5p shares the 7-nt seed sequence with miR-146a-5p, which belongs to the miR-146 family, known to be involved in the inhibition of macrophage-induced apoptosis, angiogenesis activation [26], and metastasis formation in renal cell cancer [27]. And miR-106b-5p shares the 7-nt seed sequence with miR-17-5p, which belongs to the miR-17-92 cluster family, and is implicated in a wide variety of malignancies [28]; for example, miR-106b-5p activates cell proliferation and inhibits apoptosis in non-small cell lung cancer [29].…”
Section: Discussionmentioning
confidence: 99%